Why State-Owned Enterprises Often Do Earnings Management? - Wuri Cahyaning Pramusti; Elva Nuraina; Elana Era Yusdita (AKRUAL: JURNAL AKUNTANSI, 2022)
The requirement that the income statement provided be in the profit position all of the time encourages the use of earnings management. Managers manipulate data using accounting practices to fool stakeholders. The goal of this research is to see how the effect of government ownership on earnings management affects audit quality. For 2015-2020, the population is State-Owned Enterprises listed on the IDX. A sample of 24 State-Owned Enterprises is obtained using the purposive sampling method. Using EViews version 10, simple regression and moderated regression analysis (MRA) were used to analyze the data. The findings reveal that government ownership has no effect on earnings management and that audit quality has no effect on earnings management when it comes to government ownership. Big Four public accounting firms have been unable to curb earnings management practices due to government expectations and protection. The bank's earnings management profit maximization occurred as a result of the bank's desire to attract and increase the confidence of third-party funds, which are the bank's greatest source of funds. Income minimization, on the other hand, occurred because the corporation intended to lower the amount of tax it had to pay to the government.